2014
DOI: 10.1074/jbc.m114.572883
|View full text |Cite
|
Sign up to set email alerts
|

FAD2 and FAD3 Desaturases Form Heterodimers That Facilitate Metabolic Channeling in Vivo

Abstract: Background: Plant fatty acid desaturase (FAD) enzymes determine the desaturation status of plant lipids. Results: FAD enzymes form homo-and heterodimers; FAD2-FAD3 heterodimers can channel oleate to linolenate without releasing the linoleate intermediate. Conclusion:A physiological function for FAD2-FAD3 heterodimers has been demonstrated. Significance: That monoenes can be channeled to trienes has implications for engineering desired plant fatty acid compositions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 40 publications
(25 reference statements)
6
52
0
1
Order By: Relevance
“…To our knowledge, this study is the first report to generate transgenic C. sativa plants with enhanced oil content of seeds. In addition, there is a significant increase in the levels of 18:2 plus 18:3 in T1 T2 T3 T4 T5 T6 T7 T8 T9 T10 T11 16:0 18: (Lou et al 2014). It was observed that the levels of seed oils increased by approximately 10-20 % in T 4 seeds of transgenic Arabidopsis overexpressing AtWRI1 (Cernac and Benning 2004).…”
Section: Discussionmentioning
confidence: 78%
“…To our knowledge, this study is the first report to generate transgenic C. sativa plants with enhanced oil content of seeds. In addition, there is a significant increase in the levels of 18:2 plus 18:3 in T1 T2 T3 T4 T5 T6 T7 T8 T9 T10 T11 16:0 18: (Lou et al 2014). It was observed that the levels of seed oils increased by approximately 10-20 % in T 4 seeds of transgenic Arabidopsis overexpressing AtWRI1 (Cernac and Benning 2004).…”
Section: Discussionmentioning
confidence: 78%
“…The increase in 18:2n-6 at the expense of 18:3n-3 suggests that the usage of 18:2n-6 by PDAT supersedes that of FAD3, and 18:2n-6 is to a high degree removed from PC by PDAT before it is desaturated to 18:3n-3. Thus, in C. sativa, FAD2/ FAD3 heterodimer formation to form 18:3n-3 directly from 18:1n-9 without the intermediate release of 18:2n-6 (Lou et al, 2014) does not seem to be a major pathway. The reason for 18:2n-6 being increased dramatically in TAG could be that the enzyme has a specificity for either or both 18:2n-6-containing DAG and PC as a substrate.…”
Section: Pdat Overexpressionmentioning
confidence: 99%
“…The enzymes that are primarily responsible for producing PUFAs in seed oils are the microsomal v-6 and v-3 fatty acid desaturases FAD2 and FAD3, which act in sequence to convert oleic acid (18:1) to linoleic acid (18:2) and then to a-linolenic acid (18:3), while the fatty acid is esterified to the sn-2 position of PC (Miquel and Browse, 1992;Browse et al, 1993;Lou et al, 2014). Temperature can influence the degree of microsomal fatty acid desaturation indirectly through its effects on substrate availability (Harris and James, 1969;Browse and Slack, 1983;Rolletschek et al, 2007;Li et al, 2015).…”
mentioning
confidence: 99%